(untitled) (Politeja, 2022)
The article describes the transformation of the Russian coercive apparatus (comprising security services and the military) after Vladimir Putin came to power. The different forces charged with ensuring domestic and external security of the state are one of the cornerstones of Putin’s presidency. The first stage of the changes saw them consolidated and brought under tighter control of the president’s camp, whilst during the second – following Putin’s re-election as president in 2012 – they were much expanded and modernised. Looking mainly at the normative acts from that period, the article discusses the scope and nature of these changes as well as their wider political context related to the development of a centralised, authoritarian power system in Russia. It also focuses on the parallel process of changes introduced in the prosecutor’s office and the justice system whose aim – like in the case of the coercive apparatus – was to extend the power of the president and strengthened the state’s control over society.